Diseño de un modelo de logística inversa para llantas. Una aplicación en proyectos de construcción de vivienda de interés social en Bogotá D.C. (2018)
Reverse logistics as a method of planning, control and implementation of both physical flow and information, is a fundamental part of this research, this is how a theoretical, conceptual, legal and historical framework is created, where in conclusion an analysis of the tire return management in the city of Bogotá and the possible uses of the tire as a construction material. Identifying these elements proceeds to make a diagnosis and analysis of it, where results from primary and secondary sources are confronted by hypotheses identifying the elements for the creation of the model. Finally, its construction is where the social, environmental and economic benefits that this research will bring are quantified.